2017
DOI: 10.22159/ajpcr.2017.v10i11.20528
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Blood Pressure and Pupil to Limbus Diameter Ratio in Hypertensive Women: A Pilot Study

Abstract: Objective: This study was undertaken to observe the relationship between blood pressure (BP) and pupil to limbus diameter (PLD) ratio in hypertensive working women.Methods: A total of 30 hypertensive working women were part of the study after obtaining written, voluntary, informed consent, and ensuring confidentiality. PLD ratio was measured by two-box method as described in the literature. Results:Positive correlation was observed between PLD ratio of the right eye (r=0.951) and left eye (r=0.927) and systoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…9 Earlier studies reported a positive correlation between the PLD ratio and blood pressure and pulse rate. [10][11][12][13] The ratio can be measured by the two-box method. The pupil dilation and constriction are regulated by the autonomic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Earlier studies reported a positive correlation between the PLD ratio and blood pressure and pulse rate. [10][11][12][13] The ratio can be measured by the two-box method. The pupil dilation and constriction are regulated by the autonomic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this may be the earlier studies conducted were only in one gender either male or female. 13,14 However, the current study included both genders. Further, as female participants were involved in this, there may be the influence of cyclical changes in the hormones on autonomic activity.…”
Section: Discussionmentioning
confidence: 99%